Hubungan Pengetahuan Dan Sikap Tentang HIV/AIDS Terhadap Pemeriksaan Provider Initiated Testing And Counseling (PITC) Ibu Hamil Di Puskesmas Lemoe - Harmawati Rustan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
HIV/AIDS is a global health problem that remains a serious concern, especially in Parepare, which has a relatively high prevalence of cases. Pregnant women are considered a high-risk group because they can transmit HIV to their babies during pregnancy, childbirth, and breastfeeding. One preventative measure is Provider-Initiated Testing and Counseling (PITC) testing, which allows for early detection and counseling for pregnant women. However, its success is influenced by the mother's level of knowledge and attitudes. This study aims to determine the relationship between knowledge and attitudes about HIV/AIDS and PITC testing among pregnant women at the Lemoe Community Health Center in 2025. This study was quantitative with a cross-sectional design. A sample size of 50 pregnant women was selected using a purposive sampling technique. The research instrument was a questionnaire to measure knowledge and attitudes, and PITC testing data was obtained from the Community Health Center records. Data analysis was performed using the Chi-Square test at a significance level of α = 0.05. The results showed that the majority of respondents had good knowledge (60%), a positive attitude (64%), and the majority (70%) were willing to undergo PITC testing. A chi-square test showed a significant relationship between knowledge and PITC testing (p < 0.001) and attitude and PITC testing (p < 0.001). The conclusion of this study is that pregnant women's knowledge and attitudes are significantly related to their willingness to undergo PITC testing. Therefore, increasing education, counseling, and family support is crucial to expanding PITC coverage as an effort to prevent mother-to-child HIV transmission.